Patient‐Reported Selective Adherence to Heart Failure Self‐Care Recommendations: A Prospective Cohort Study: The Atlanta Cardiomyopathy Consortium. Issue 1 (9th September 2012) - Marti, Catherine N.; Georgiopoulou, Vasiliki V.; Giamouzis, Grigorios; Cole, Robert T.; Deka, Anjan; Tang, W. H. W.; Dunbar, Sandra B.; Smith, Andrew L.; Kalogeropoulos, Andreas P.; Butler, Javed
Abstract : ©2012 Wiley Periodicals, Inc. Simultaneous adherence with multiple self‐care instructions among heart failure (HF) patients is not well described. Patient‐reported adherence to 8 recommendations related to exercise, alcohol, medications, smoking, diet, weight, and symptoms was assessed among 308 HF patients using the Medical Outcomes Study Specific Adherence Scale questionnaire (0="never" to 5="always, " maximum score=40). A baseline cumulative score of ≥32/40 (average ≥80%) defined good adherence. Clinical events (death/transplantation/ventricular assist device), resource utilization, functional capacity (6‐minute walk distance), and health status (Kansas City Cardiomyopathy Questionnaire [KCCQ]) were compared among patients with and without good adherence. The mean follow‐up was 2.0±1.0 years, and adherence ranged from 26.3% (exercise) to 89.9% (medications). A cumulative score indicating good adherence was reported by 35.7%, whereas good adherence with every behavior was reported by 9.1% of patients. Good adherence was associated with fewer hospitalizations (all‐cause 87.8 vs 107.6; P =.018; HF 29.6 vs 43.8; P =.007) and hospitalized days (all‐cause 422 vs 465; P =.015; HF 228 vs 282; P <.001) per 100‐person‐years and better health status (KCCQ overall score 70.1±24.6 vs 63.8±22.8; P =.011). Adherence was not associated with clinical events or functional capacity. Patient‐reported adherence with HF self‐care recommendations is alarmingly low and selective. Good adherence was associated with lower resource utilization and better health status.